Quality management practices and sustainable performance: examining the role of soft TQM as mediator - Khalili, Amjad; Ismail, Md Yusof; Karim, A.N. Mustafizul; Che Daud, Mohd Radzi (Inderscience Enterprises Ltd., 2019)
Malaysian managers are trying to implement quality management (QM) practices in their industries to be competitive. However, few empirical studies are conducted in the developing economy of Malaysia to examine the role of TQM soft dimension (STQM) as possible mediator in the relationship among QMS ISO9001:2015 and sustainable performance (SP). Using 329 primary data collected from Malaysian numerous industries, this paper aims to develop a conceptual model that links the three practices namely QMS, STQM and SP in one integrated model and to examine the mediating structure of soft TQM (STQM) aspects through techniques exploited from structural equation modelling (SEM). Findings from AMOS program show that bootstrapping technique supported that STQM is treated as mediator construct. Full mediation is detected in this paper which reflects the importance of practising STQM aspects for Malaysian manufacturers. The main contribution of this paper is through introducing bootstrapping for mediating estimation and focusing on all measured industrial sectors that Malaysia needs to be an industrialised nation in the coming few years.